2015
DOI: 10.1007/s13277-015-3553-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AURKC expression by CpG island methylation in human cancer cells

Abstract: AURKC, a member of the Aurora kinase gene family, is highly expressed in testis but is either moderately expressed or repressed in most somatic cells. Varying expression of AURKC has been observed in human cancers, but the underlying mechanisms of differential expression have been investigated only to a limited extent. We investigated the role of promoter CpG methylation in the regulation of AURKC gene expression in human cancer cells, in relation to a recently reported AURKC transcription repressor PLZF/ZBTB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The findings that Aurora-C expression is elevated in multiple human cancers indicates a functional role for the kinase in adult somatic tissues and makes it imperative that the molecular details of Aurora-C interactions with the CPC components and the functional consequences of Aurora-C over expression in cancer cells be well elucidated. It is relevant in this context that we have recently reported transcriptional down-regulation of AURKC locus due to hyper-methylation of CpG islands in the promoter to be primarily responsible for low expression of Aurora-C in adult somatic tissues and cell lines in vitro [ 32 ]. Our study further revealed that CpG hypo-methylation besides down-regulation of the previously published transcriptional repressor PLZF/ZBTB16 [ 33 ] is associated with elevated expression of Aurora-C in human cancer cells, also validated in The Cancer Genome Atlas (TCGA) data set across different human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The findings that Aurora-C expression is elevated in multiple human cancers indicates a functional role for the kinase in adult somatic tissues and makes it imperative that the molecular details of Aurora-C interactions with the CPC components and the functional consequences of Aurora-C over expression in cancer cells be well elucidated. It is relevant in this context that we have recently reported transcriptional down-regulation of AURKC locus due to hyper-methylation of CpG islands in the promoter to be primarily responsible for low expression of Aurora-C in adult somatic tissues and cell lines in vitro [ 32 ]. Our study further revealed that CpG hypo-methylation besides down-regulation of the previously published transcriptional repressor PLZF/ZBTB16 [ 33 ] is associated with elevated expression of Aurora-C in human cancer cells, also validated in The Cancer Genome Atlas (TCGA) data set across different human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially from AURKA and AURKB, Aurora kinase C (AURKC) is limited to cells that undergo meiosis (sperm and oocyte). This kinase is located on human chromosome 19q13.43, regulated by promoter methylation and when expressed in germ cells, can undergo alternative splicing resulting in three protein variants [ 561 , 562 , 563 ]. As the major enzymatic component of the CPC during meiosis, it plays a specific role during human female meiosis and preimplantation embryo development [ 564 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%
“…In terms of their role as mitotic regulators, deletion of AURKs could lead to cell division failure and embryonic development impairment. Increased expression or gene amplification of AURKs has been described in numerous cancers 158 , including breast 159,160 , ovarian 161,162 , gastric/gastrointestinal 163,164 , colorectal 165,166 , lung 167,168 , cervical 169,170 , prostate 160,171,172 , oral 173,174 , AML 175,176 , and glioma 177,178 . Importantly, in glioma tumors, AURKA and AURKB expression increases with tumor grade, 179-182 , and is significantly associated with GBM poorer patient survival 183-185 .…”
Section: Targeted Therapy Against G2/m Regulatorsmentioning
confidence: 99%